Alignment of Public Administration-Focused Undergraduate Programs with Career Opportunities in Government Bodies in Azerbaijan - Hasanova, Saad; Mammadov, Ramil; Jahangirova, Solmaz; Mammadzada, Aydan; Allahverdiyeva, Aysel (ADA University, 2025)
This capstone project explores the alignment between public administration-focused undergraduate programs offered by public universities and the career requirements of government bodies in Azerbaijan. Through a qualitative methodology involving semistructured interviews with recent graduates of the programs and representatives from government bodies, and reviews of relevant documents provided by a public university, the research identifies the gaps between skills and competencies obtained through the given education programs and job requirements in the government bodies. The key findings highlight a limited emphasis on practical skills, with the public administration-focused undergraduate programs placing greater focus on theoretical knowledge. Moreover, data analysis revealed misalignment between the Civil Service Exam operated by the State Examination Center and the learning outcomes of the programs. The research highlights the importance of integrating practice-based learning, stronger university-government collaboration, and improvement of the relevant programs in public universities. Recommendations include revising the content of the education programs to better reflect their relevance to the job requirements, incorporating internships and practice-based projects. The implications of this research are vital for bridging collaboration between the universities’ relevant programs and the government bodies for enhancing a competent, career-ready public administration workforce in Azerbaijan. Based on the findings, we propose a website to be created, aiming to improve the collaboration between the undergraduate programs and careers in the government bodies. The website will provide an opportunity for the students of the undergraduate programs to gain practical experience through the internship programs, workshops, and different trainings, which will be organized by the government bodies
Keywords: Public administration -- Study and teaching (Higher) -- Azerbaijan; Education, Higher -- Curricula -- Azerbaijan; Civil service -- Examinations -- Azerbaijan; Career development -- Azerbaijan; Experiential learning -- Azerbaijan; Education